Guatemalan “Justice Centers”: The Centerpiece for Advancing Transparency, Efficiency, Due Process, a - Steven E. Hendrix (My University, 2016)
This paper examines the US Agency for International Development (USAID) model of the Justice Center in Guatemala, an effort to bring together police, prosecutors, judges, public defenders, local civil society, and private law practitioners to solve problems in a collaborative framework. Hendrix provides a detailed explanation of the Justice Centers and what has made them a relatively effective solution for Guatemala.